Forming Critical Thinking Concepts in Students - Barasa, Tiurma (LP. Ma'arif Janggan Magetan, 2022)
The concept of critical thinking that comes from an understanding of concepts can be formed through providing real examples accompanied by material explanations. This ability is a cognitive skill in translating, interpreting, and re-explaining concepts in its own way. It also refers to the ability to explain a concept that has been understood in the form of oral or written explanation to others. Students' low understanding of a concept affects students' ability to solve more complex problems. The low ability of students to think critically is reflected in the weak ability of students to rebuild a concept, provide practical examples, and apply a concept to solve problems. This study aims to prove the positive influence of students' critical thinking skills on affective learning outcomes. The research design used in this study is a causality research design. As part of quantitative research, data are obtained through random sampling. The sample taken must be completely representative because the conclusions drawn from the sample will apply to the population. Therefore, this study used a sample of 50 students. Through field tests, it was concluded that critical thinking skills can affect students' affective learning outcomes by 43,8%. The learning outcomes are illustrated by the participants the more understanding, the more sensitive, the better, and the more professional they are in doing something, as a result of learning in the affective realm.